(untitled) (Bangladesh Journal of Urology, 2020)
Introduction: Direct Visual Internal Urethrotomy (DVIU) is the most commonly used technique for short segment bulbar urethral stricture till date. But it has a high failure and recurrence rate. On the other hand, urethroplasty is regarded as the gold standard treatment for urethral stricture. Moreover, for bulbar urethral stricture, usually more than 3cm stricture are treated with substitution urethroplasty. Current practice for short segment bulbar urethral stricture is multiple sessions of DVIU and then buccal mucosal graft (BMG) urethroplasty if they fail. But repeated DVIU make the stricture segment longer and more fibrotic. Considering the morbidities following repeated DVIU, this prospective clinical trial has been designed to compare the outcome of BMG urethroplasty after failed urethrotomy versus primary repair. Objective: To determine stricture recurrence, PVR and flow of urine in between primary BMG urethroplasty group and after failed DVIU group. Patients and Methods: The present study was conducted in the department of Urology, BSMMU between July’15 - February’17. Patients of short segment bulbar urethral stricture between 1.5- 3 cm without any previous DVIU were enrolled as study group(n=22) and patients with history of failed DVIU were included as control group(n=22). All the patients were followed upto 12 months after BMG urethroplasty and recurrence of stricture (by RGU and MCU), PVR and maximum urine flow rate (Qmax) in between two groups were compared. Results: The stricture recurrence rate was found significantly higher in control group than in the study group (p=0.042). The study group showed highly significant (0.000) decrease in post-operative PVR and significant (0.009) increase in post operative maximum urine flow rate than the control group as was assumed in the hypothesis. Conclusion: The present study propose that BMG urethroplasty as primary repair for bulbar urethral stricture within a length of 1.5-3 cm in younger age group (upto 45 years ) is very effective than BMG urethroplasty after failed DVIU cases. But long term multicentric trial is needed to further comment. Bangladesh Journal of Urology, Vol. 21, No. 1, January 2018 p.3-7